First- and second-sphere co-ordination of a lanthanum cation by a calix[4]arene tetraamide in the partial-cone conformation - Beer, P; Drew, M; Ogden, M (1997)
5,1 l,17,23-Tetra-/er/-butyl-25,26,27,28-tetrakis(diethylcarbamoylmethoxy)calix[4] arene (L) has been synthesized in the partial-cone conformation for the first time. Reaction with lanthanum picrate (2,4,6-trinitrophenolate) gives a 1:1 complex which has been structurally characterised: [LaL(pic)3(H2O)2]'3H2OMeCN (triclinic, space group PI, Z = 2, R = 0.087 for 10 150 independent reflections above background). The metal-calixarene interactions involve two amide oxygen atoms in the first co-ordination sphere and three oxygen atoms (two ether and one amide) in the second. The remainder of the first co-ordination sphere of the nine-co-ordinate lanthanum cation consists of two water oxygen atoms and oxygen atoms of the three picrate anions.